ANALYSIS OF THE COMPANY'S FINANCIAL PERFORMANCE BEFORE AND AFTER THE CONSUMER BOYCOTT CAMPAIGN (CASE STUDY OF PT. MAPB TBK) PERIOD 2022 – 2024 - Victorson Taruh; Nurharyati Panigoro; Sisna Meamogu; Yusuf Abdul Wahid (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the differences in the financial performance of PT MAP Boga Adiperkasa Tbk (MAPB) before and after the consumer boycott campaign in the 2022–2024 period. The boycott campaign triggered by global geopolitical issues has an impact on the decline of the company's social legitimacy, thus affecting profitability and financial stability. The research method uses a descriptive quantitative approach through the analysis of annual financial statements processed using profitability ratios. The results show a significant downward trend in the entire profitability ratio from 2022 to 2024. In 2022, the entire ratio was in a positive condition, but declined sharply in 2023 and turned negative in 2024; NPM from 4.26% to −4.53%, ROA from 5.67% to −4.93%, ROE from 12.45% to −9.45%, and ROI from 8.37% to −4.87%. These findings indicate that boycott campaigns have a significant effect on declining profitability and show the loss of corporate social legitimacy in the eyes of the public according to the perspective of legitimacy theory.